Preoperative glucose abnormalities in patients with pancreatic tumours - Matejak-Górska, Marta A.; Durlik, Marek; Kałuża, Bernadetta; Milczarczyk, Alicja; Franek, Edward (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Pancreatic cancer is a neoplasm characterised by poor prognosis. The only effective, possible treatment is radical surgery, but most patients do not qualify for surgery because of delayed diagnosis. Aim : To determine if assessment of endocrine pancreatic function could serve as a means of screening for pancreatic cancer. Material and methods: This prospective study was conducted on a group of 50 patients diagnosed with pancreatic tumour, who were qualified for surgery. Results: From 1.07.2010 to 4.07.2011 a further 50 patients were added to the study group. They had been admitted to the hospital with pancreatic tumours. During the preoperative period, nine of these people had been treated for diabetes, 14 were newly diagnosed with diabetes and 15 had been diagnosed with impaired glucose tolerance, but only 12 had a normal glucose profile. Afterwards, patients underwent the surgical treatment. Histopathological examination revealed that out of the 50 operated patients, 36 suffered from malignant disease, and of these only four had no impaired glucose tolerance before treatment. Conclusions : In most cases, patients with pancreatic tumours have impaired glucose tolerance. Screening patients over 50 years of age could speed up diagnosis and surgical treatment.